Choice of Innovative Technologies as a Factor of Modernization of the Industrial Plants - E. A. Panfilova (Vestnik MGIMO-Universiteta, 2015)
The article analyzes the need to develop a new type of interaction between providers of the equipment and its end-users in a changing social and cultural reality. This type of interaction is a guarantee of innovative modernization of Russian industrial facilities, as it is based on a revision of the social reality in light of new information and/or knowledge. The choice of innovative technologies that contribute to fruitful and qualitative relationships among the actors of the social process acquires significance since there have been changes in the role, objectives and potential of technology. The author focuses on the changes in perceptions of social time and space, reflection of consumers (the impact of economic, social and psychological factors on their decision to purchase), and suppliers. There is a reflection of the habitus of social actors in the context of social interaction, based on the organization of innovative practices. Today technology is also reflecting, its symbolic characteristics, contained in the codes of signification, become more important, than technical ones. The research is based on in-depth interviews with experts from the pharmaceutical industry aimed at identifying the factors influencing the decision to purchase an innovative high-quality imported equipments and machinery, which would contribute to the modernization of the existing production process. The author concludes that adequate reflection which promotes the creation and dissemination of new social practices based on close and confidential contacts and development of flexible communication tools would provide for successful modernization of Russia.